High-contrast X-ray micro-radiography and micro-CT of ex-vivo soft tissue murine organs utilizing ethanol fixation and large area photon-counting detector - Dudak, Jan; Zemlicka, Jan; Karch, Jakub; Patzelt, Matej; Mrzilkova, Jana; Zach, Petr; Hermanova, Zuzana; Kvacek, Jiri; Krejci, Frantisek (Scientific reports, 2016)
Using dedicated contrast agents high-quality X-ray imaging of soft tissue structures with isotropic micrometre resolution has become feasible. This technique is frequently titled as virtual histology as it allows production of slices of tissue without destroying the sample. The use of contrast agents is, however, often an irreversible time-consuming procedure and despite the non-destructive principle of X-ray imaging, the sample is usually no longer usable for other research methods. In this work we present the application of recently developed large-area photon counting detector for high resolution X-ray micro-radiography and micro-tomography of whole ex-vivo ethanol-preserved mouse organs. The photon counting detectors provide dark-current-free quantum-counting operation enabling acquisition of data with virtually unlimited contrast-to-noise ratio (CNR). Thanks to the very high CNR even ethanol-only preserved soft-tissue samples without addition of any contrast agent can be visualized in great detail. As ethanol preservation is one of the standard steps of tissue fixation for histology, the presented method can open a way for widespread use of micro-CT with all its advantages for routine 3D non-destructive soft-tissue visualisation.
Keywords: ethanol; Lung; ledviny; myši; zvířata; Ethanol; plíce; X-Ray Microtomography; rentgenová mikrotomografie; Heart; Kidney; Animals; Mice; Mice, Inbred C57BL; Photons; fotony; srdce; myši inbrední C57BL